Pengembangan E-LKPD Berbasis Inkuiri Berbantuan Articulate Storyline Tema 6 Subtema 1 Pembelajaran 1 Kelas IV SD Negeri 018092 Lobu Rappa T.A 2022/2023 - Simbolon, Mariana Olandri; Ananda, Lala Jelita; Simbolon, Naeklan; Siregar, Arifin; Parangin-Angin, Laurensia M. (Journal of Student Development Information System (JoSDIS), 2023)
The background of this research is the unavailability of E-LKPD which is able to attract students' interest in learning in grade IV SD. This study aims to produce Inquiry-based E-LKPD assisted with articulate storytelling that is valid, practical and effective in supporting learning success. This research is research and development using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The subject of this research was class IV students at SDN 018092 Lobu Rappa and the object of this research was an inquiry-based E-LKPD with the aid of an articulate storyline. The results showed that the validation by stage I material experts before revision obtained a percentage of 68% in the category "Easy with Revision" then in stage II obtained a percentage of 89.3% in the category "very feasible without revision" and the results of the design validation stage I obtained a percentage of 55% "Enough Feasible with Revision" then in stage II obtaining a percentage of 63.75% in the category "very feasible with revision" then stage III obtaining a percentage of 86.25% in the category "very feasible without revision". Practical trials by education practitioners obtained a percentage of 96% in the "very practical" category and the results of student responses in field trials in individual trials obtained 93% results, in small group trials obtained a percentage of 97% and large group or field trials obtained results percentage of 98%. The results of the media effectiveness test through the pretest obtained an average of 33.33 with the "Not Complete" completeness criterion while in the posttest obtained an average of 88.125 with the "Complete" completeness criteria. It can be concluded that the product developed is very feasible, practical and effective for use in learning in elementary schools.